A parceria público-privada como instrumento urbanístico: o caso do município de São Paulo-SP - Guilhen, Adriana Jesus (2014)
The Federal Constitution constitutes instruments that emphasize the social purpose of the land, regulated by the City Statute; compounded by municipal responsibilities that sometimes have no corresponding item in tax collection, creating budgetary constraints that hamper investments. Combined technical and administrative obsolescence of the contemporary state, the public-private partnership is an important tool for urban reform with private funding, under the cloak of a distributive character. But the obstacles are many. Despite the existence of an important legal framework, it is not, in Brazil, a tradition of the private sector to invest in social works as the housing market is restricted. The success of the partnership depends on a paradigmatic shift in public policy: it will aim at social justice or continue to succumb to real estate speculation. Based on this background, the objective of this study is to analyze the public-private partnership within the bounds of the country's urban policy, to understand this instrument forseen in the City Statute through the analysis of its legal framework and with European experiences, with the empirical object of its application through urban operations in the São Paulo municipality. Methodology: exploratory, descriptive and explanatory; to deepen the theoretical and empirical knowledge about the situation of the problem and the analysis that was done with legislation and bibliography, constituting the major source of evidence. Results: During the analysis of the Brazilian urban reform, state administrative and technical obsolescence and limitations of public resources were observed, occupying a prominent position in public-private partnership in urban reform, and how it could be analyzed together with the European experience of social innovation, especially in the São Paulo municipality. Despite the social, economic, environmental and political appeals present in the partnership, the literature highlights contradictions and obstacles for its consolidation as an alternative to urban development based on social inclusion as well as to pay attention to the diversion of its purpose, as the practice has prioritized real estate capital. It is pertinent to note the importance of the private sector s participation in urban development, because despite the state mandate, due to its technical, administrative and financial constraints, the government has encountered obstacles in complying with this proposition. Conclusion: In this context, one of the challenges is to provide measurement tools to provide information for the evaluation of urban development in order to define the applicability of the public-private partnership, which may materially have an impact, directly or indirectly, negatively or positively, if used as an instrument of government or state policy. The legal framework deserves only a few adjustments to make the partnership attractive to the private sector and at the same time encourage fairness; however, it has not been enough to make the partnership viable given the complexity and contradictions of capitalist urbanization. Accordingly, it is hoped that the government and the private sector will be compelled to seek adequate ways of carrying out a public-private partnership, with management focused on the areas of social justice.